2019
DOI: 10.1210/js.2018-00414
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian Hormone Levels and Cardiometabolic Disturbances by Weight Status Among Men in the 1999 to 2004 National Health and Nutrition Examination Survey

Abstract: Context Serum anti-Müllerian hormone level (AMH) and body mass index may be jointly associated with cardiometabolic risk. Objectives Examine the contribution of AMH to cardiometabolic disturbances by weight status among US adult men. Design Cross-sectional analysis using data from the 1999 to 2004 waves of the National Health and Nutrition Examination Survey. Setting Multistage probability sampling of the noninstit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
5
8
0
Order By: Relevance
“…Our in‐house reference range obtained from a different population of 40 adult fertile nonobese men aged 24‐40 years was 35‐305 pg/mL or ng/L. These values are in line with other studies that used the same kit . As reported in our previous study, serum steroid hormones were measured by liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) using reference intervals in healthy adult men by Fanelli et al Gonadotropins and sex hormone‐binding globulin (SHBG) were measured at the Central Laboratory of S.Orsola Malpighi Hospital (Bologna, Italy) by Modular Analytics E 170 (Roche Diagnostics) and by Immulite 2000 (Siemens Healthcare Diagnostics), respectively, as previously described …”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…Our in‐house reference range obtained from a different population of 40 adult fertile nonobese men aged 24‐40 years was 35‐305 pg/mL or ng/L. These values are in line with other studies that used the same kit . As reported in our previous study, serum steroid hormones were measured by liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) using reference intervals in healthy adult men by Fanelli et al Gonadotropins and sex hormone‐binding globulin (SHBG) were measured at the Central Laboratory of S.Orsola Malpighi Hospital (Bologna, Italy) by Modular Analytics E 170 (Roche Diagnostics) and by Immulite 2000 (Siemens Healthcare Diagnostics), respectively, as previously described …”
Section: Methodssupporting
confidence: 82%
“…These values are in line with other studies that used the same kit. 12,17 As reported in our previous study, 9 serum Diagnostics), respectively, as previously described. 19…”
Section: Assessments and Measurementsmentioning
confidence: 99%
“…The generalisability of this finding may be limited, as it has been suggested that circulating AMH levels temporarily drop during late-stage pregnancy [ 34 ]. In line with our results, a previous study in men observed a lower risk of type 2 diabetes in overweight individuals with higher AMH levels [ 35 ]. In men, AMH is produced by Sertoli cells and also decreases with increasing age [ 36 ], although to a lesser degree than in women.…”
Section: Discussionsupporting
confidence: 93%
“…The generalisability of this finding may be limited, as it has been suggested that circulating AMH levels temporarily drop during late-stage pregnancy [34]. In line with our results, a previous study in men observed a lower risk of type 2 diabetes in overweight individuals with higher AMH levels [35]. In men, AMH is produced by Sertoli cells and also decreases with increasing age [36], although to a lesser degree than in women.…”
Section: Discussionsupporting
confidence: 80%